Аналіз теплового стану різних модифікацій рудникового тягового двигуна постійного струму типу ДТН-45/27 - Шайда, Віктор Петрович; Юр'єва, Олена Юріївна; Дзеніс, Сергій Євгенович (НТУ "ХПІ", 2017)
Проведено дослідження можливостей підвищення годинної потужності тягових двигунів постійного струму типу ДТН-45/27. Встановлено, що основним обмежувачем підвищення потужності є тепловий стан двигуна. Шляхом фізичного моделювання виконано оцінку теплового стану різних модифікацій двигуна. Визначено тупикові напрямки модифікації двигуна, визначено шляхи подальших досліджень.

Studies were made of the possibilities of increasing the hourly power of traction motors of direct current type ДТН-45/27. Methodology. Physical simulation of the DC motor was made to determine the influence of the geometry of the collector on the motor thermal state. Excess temperature of windings of the motor was measured by the method of resistance, collector and bearings – by the method of the thermometer Results. The results of the tests of the thermal state of the traction motor of the main modification, with the improved fan, with the shortened collector, have been obtained. The influence of modifications on the temperature of windings, collector and bearings of the motor has been analyzed. Originality. For the first time results of tests of the thermal state of traction motors of DC type ДТН 45/27 of different modifications were obtained. The greatest excess temperature in certain parts of the engine was determined. Practical value. It is proposed to consider variants of cooling (motor ventilation system) of the engine. For example, apply a two-circuit cooling system or install a motor-fan instead of an ordinary fan. It is proposed to apply axial ventilation ducts in the anchor, which will allow the flow of cold air through the core, under the front parts of the winding of the anchor and under the collector. This should solve the problem of temperature drop across the length of the anchor core and more effectively cool the collector.
Analysis of the thermal state of various modifications of the mining traction motor DC type ДТН-45/27
Keywords: електричні машини; рудниковий контактний електровоз; годинна потужність; система вентиляції; перевищення температури; miner contact electric locomotive; traction motor DC; hourly power; ventilation system; thermal state; temperature rise